Essence and principles of the method of group economic standards for calculation the cost of medical care in hospital - Baieva, Olena; Baiev, Vadim (My University, 2021)
The method of group economic standards of health care was developed in the 70s of the last century at Yale University and introduced in the United States in 1983 as a basic basis for payment for medical services in the system "Medicare". 467 clinical and statistical groups became the initial medical and economic base. The criteria for their selection were: homogeneity of diseases and homogeneity of medical and diagnostic procedures; homogeneity of volumes and structure of resources used at treatment.
Keywords: кафедра туристичного та готельного бізнесу; wellness services; business processes; medical tourism; medical services; медичний туризм; медичні послуги; оздоровчі послуги; ділові процеси